Keharusan Ikrar Talak di Depan Majelis Hakim Pengadilan Agama : Perspektif Maqāṣid Syarī’ah Ibnu ‘Āsyūr - ludfi (MAQASHID Jurnal Hukum Islam, 2023)
This study aims to elaborate on the provisions of divorce in classical fiqh which are considered valid simultaneously when pronounced by the husband, while in positive law they are only considered valid when pronounced by the husband before the court. Both of them gave rise to a "dilemmatic" law among Indonesian Muslims, so that maqāṣid syarī'ah was present as a "peacemaker" through the perspective of Ibnu 'Āsyūr. This type of research is library research with content analysis, philosophical-hermeneutic and maqāṣid syarī'ah approaches. The data collection technique is in the form of documentation through inventory, classification and evaluation of data. The findings of this study indicate that there are aspects of maṣlaḥaḥ of having to pledge divorce before the Panel of Judges of the Religious Courts: equality before the law and legal certainty (status and wife's maintenance, joint assets, hadlanah rights and guarantee for children's maintenance). Ibn 'Āsyūr with his four pillars al-Fiṭrah, as-Samāhah, al-Musāwah and al-Hurriyah as the main foundations in his maqāṣid syarī'ah building requires the presence of divorce witnesses in interpreting QS. aṭ-Ṭalāq (65) verse (2) via ẓāhir naṣ. This interpretation has relevance to the obligation to pledge divorce before the court; before the Panel of Judges of the Religious Courts as a provision of positive law in Indonesia to make it difficult for divorce to occur as a form of maqāshid syarī'ah, although he did not directly mention that the divorce pledge must be presented before the court.